The Answerthis.io AI App Looks at My Interaction Equivalency Theory - Anderson, Terry (International Review of Research in Open and Distributed Learning, 2026)
This field note provides an example of the use of an education/researcher artificial intelligence program to provide an overview of the Interaction Equivalency Theory. This theory was first presented as an example in Anderson, T. (2003), "Getting the mix right again: An updated and theoretical rationale for interaction", in the International Review of Research in Open and Distributed Learning, 4(2). The AI tool provides a useful synopsis and overview of the value of this theory for distance education students and researchers.